2021
DOI: 10.3389/feduc.2021.639338
|View full text |Cite
|
Sign up to set email alerts
|

What Questions Are on the Minds of STEM Undergraduate Students and How Can They Be Addressed?

Abstract: Addressing common student questions in introductory STEM courses early in the term is one way that instructors can ensure that their students have all been presented with information about how to succeed in their courses. However, categorizing student questions and identifying evidence-based resources to address student questions takes time, and instructors may not be able to easily collect and respond to student questions at the beginning of every course. To help faculty effectively anticipate and respond to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Among the available options, our choice was to perform a reciprocal interview activity, as explained in detail in Section 2.1. This activity has been carried out successfully in different sessions during the first day of class of a subject [17,20,36], in line with other research studies that have found that asking the students the proper questions may be very effective [25,37]. It should be noted that it is out of the scope of this study to compare the reciprocal interview activity with a 'one-way' speech-based approach for a first day of class session.…”
Section: First Day Of Class Activities Of a Subject Mattersupporting
confidence: 65%
“…Among the available options, our choice was to perform a reciprocal interview activity, as explained in detail in Section 2.1. This activity has been carried out successfully in different sessions during the first day of class of a subject [17,20,36], in line with other research studies that have found that asking the students the proper questions may be very effective [25,37]. It should be noted that it is out of the scope of this study to compare the reciprocal interview activity with a 'one-way' speech-based approach for a first day of class session.…”
Section: First Day Of Class Activities Of a Subject Mattersupporting
confidence: 65%
“…Instructors teaching large introductory classes have a unique opportunity to assist first-year students who have recently transitioned from high school (Meaders et al, 2020). The first experiences in college can have a profound impact (Lane et al, 2021), and instructors should share effective learning strategies and time management techniques, which are known to be the most common concerns voiced by college students (Meaders et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While extensions may be created with the intent to allow students to complete their work and increase their alignment with the course goals, they may be taken advantage of to seek a higher letter grade. Students in large STEM courses have a lot of ideas and expectations (Meaders et al, 2020(Meaders et al, , 2021; therefore, the instructors' efforts in designing an unbiased extension system should be student-centered and include the analysis of student perceptions and the system's impact on final grades.…”
Section: Framing Extensions Within the Classroommentioning
confidence: 99%
“…Our results support that instructors attend to the sociocultural communities within their courses to different degrees through the use of non-content talk and that overall students detect the messages shared by their instructors. Students in introductory courses hold a variety of concerns as well as course anxiety at the beginning of the term (England et al, 2019 ; Meaders et al, 2020 ), and the first day of class and language used by instructors provides an opportunity to directly address student questions and alleviate concerns (Hsu & Goldsmith, 2021 ; Meaders et al, 2021 ). Because student perceptions of instructor support are negatively correlated with student anxiety (Schussler et al, 2021 ) and difficulty in accessing help for course work is a large factor in STEM attrition (Seymour et al, 2019 ), non-content talk on the first day of class may be a key tool instructors can use to signal support and availability for their students.…”
Section: Discussionmentioning
confidence: 99%